What Would a Tree Say About Its Size? - Larjavaara, Markku (Frontiers in Ecology and Evolution, 2021)
When developing theories, designing studies, and interpreting the results, researchers are influenced by their perception of tree size. For example, we may compare two trees of the same size belonging to different species, and attribute any differences to dissimilarities between the species. However, the meaning of “same size” depends on the measures of size used. Wood density influences certain measures, such as biomass, but does not influence e.g. trunk diameter. Therefore, the choice of the measure of size can reverse any conclusions if e.g. transpiration of an individual of species A is higher than that of an individual of species B with the same biomass but lower than that of a tree of species B with the same diameter. Hence, it is important to consider which measure of size should be used. I argue that the most common measure of size, i.e. trunk diameter, is often a bad choice when wood density varies, as diameter is then not directly related to processes important in evolution. When two trees with equal diameters but differing wood densities are compared, the tree with denser wood is larger if the measure of size is related to construction cost or trunk strength, a proxy of leaf area. From this perspective, the comparison is then conducted between a biologically larger heavy-wooded tree and a smaller light-wooded tree, and the differences between the trees may be caused by size instead of wood density. To assess how common such problems are, I reviewed ten highly cited journal articles. None of these ten articles considered the impact of wood density on biological size, which led to debatable results and gives call for reanalyzing several of them. Overall, I do not suggest avoiding the use of diameter, but I recommend considering result sensitivity to the measure of size, particularly in studies on trees with variable wood densities. Trunk biomass and strength are often more suitable measures of size, as they reflect the construction cost and biomechanical potency linked to leaf area and crown height, often too challenging to estimate more directly.